Work Fatigue and Its Associated Factors Among Sewing Workers in the Garment Industry - Raisa Shabrina Batu Bara; Nurhayati (Karya Kesehatan Siwalima, 2026)
Work fatigue is a common occupational health problem in the garment (convection) industry, particularly among sewing workers. These workers are typically required to maintain static postures for prolonged periods, work long hours, and perform monotonous, repetitive tasks. This study aims to analyze the factors associated with work fatigue among sewing workers in garment businesses located on Jalan Amaliun, Medan Area District, Medan City. The study employed a quantitative design with a cross-sectional approach. The sample consisted of 30 respondents selected using a total sampling technique. Data were analyzed using univariate and bivariate methods, with the Chi-Square test applied at a significance level of α = 0.05. The results showed significant relationships between age and work fatigue (p-value = 0.01 < 0.05), gender and work fatigue (p-value = 0.028 < 0.05), length of employment and work fatigue (p-value = 0.027 < 0.05), as well as daily working hours and work fatigue (p-value = 0.00 < 0.05). Therefore, garment workers, especially those in the sewing section, are encouraged to maintain their physical condition to remain optimal during work. Meanwhile, business owners are advised to regulate working hours more effectively and provide adequate rest periods to reduce the risk of work fatigue.